Attitudes of High Special School Students with Hearing Impairment to Online Adaptive Physical Education Learning - Rusyani, Endang; Permana, Sidik; Ragadhita, Risti (Indonesian Journal of Teaching in Science, 2022)
The research is quantitative descriptive research on the attitudes of high school students with hearing impairment towards learning adaptive physical education online in special schools based on phenomena happening right now. To find out the attitude of high school hearing impairment students towards adaptive physical education online learning, a method that was used in this research was a survey method at high special needs school in Bandung, while the data collection using a questionnaire. The results show that the attitude of high school students with hearing impairment towards online learning of physical education adaptive shows that 12.50% are included in the category very good, 12.50% included in the good category, 50% included in the category quite good, 12.50% is included in the poor category, 12.50% is included in the very poor category. Hopefully, subject teacher adaptive physical education can continue to provide motivation and understanding to students about the importance of adaptive physical education and creativity in teaching adaptive physical education though online thus students can be interested and show a very good attitude.